استخدام الشبكية في التخطيط والسيطره على جدولة تكاليف المشروع في حل البرمجة الخطية في انتاج ابواب خشب الصنوبر في معمل شركة (PINO WOOD) في محافظة دهوك. - سماهر طارق ابراه (Journal of Babylon Center for Humanities Studies, 2026)
The research aims at the process of manufacturing and producing pine wood doors produced by the company (PINO WOOD) at the lowest possible cost and a standard time rate using the method of analyzing network diagrams and linear programming, depending on the time elements and the total cost of the production process in order to prepare customer orders. The study sample was in the PINO WOOD company’s factory for producing pine wood doors in Dohuk Governorate. The study sample was in the PINO WOOD company’s factory for producing pine wood doors in Dohuk Governorate. The study came out with the following conclusions: Planning and controlling material requirements represent the essence of production systems, due to the great importance that materials represent and a high percentage of the total production costs. Planning and controlling them represents the basis for the success of operations management in achieving its goals of increasing or reducing the efficiency of resource utilization. inventory, and improve customer service, through on-time delivery and reducing delays. Perhaps one of the most important conclusions that were reached is the following. We note from the results of Table (7) that the duration of implementing a product reached (16) days, which is the period that the (PINO WOOD) factory aspires to finish producing the product according to the planning study, and that not Adopting practical methods in managing and planning production and not adhering to the critical path leads to the products not being completed within the times and costs specified for them. The duration of implementing the product (pine wood doors) It was (30) days, meaning a delay of (14) days, and the cost was $(350), meaning a difference of $(176). We note by observing Table (7) that the critical path for producing the product (pine wood doors) consists of the following critical activities: A-B-C-D-E-F-G, and that the above activities are critical activities and it is not permissible to neglect the time of their implementation. As for the rest of the activities of the process for productivity, they are non-critical activities. We note from the results of Table No. (3) that the implementation period for the (iron) product amounted to (16) days and at a cost of (174) $ using (CPM/normal time and cost time/solve critical path). We notice in Table No. (4) the balance of the total costs for all activities that start at early start times and late finish times, for example (project time in Days16) Early start time cost (cost schedule based on ES = 2.67) Late end time cost (cost schedule based on LS=12.67) Early start time (cost total based on ES=174) Late end time total cost (cost total based on lS=174) . We note in Table (5) that the actual costs and completion rates for the activities amounted to ($110). The previous table shows that activities A and B have been fully accomplished, while activities C, D, and E are still under implementation, and activities F and G have not been started yet. By using the following mathematical relationship, we find the value of the work accomplished for each activity. We note in Table (6): The costs of the actual activities that exceed the estimated costs are ($13,040). Determining the percentage of overrun is (11.85%). The current position of the project requires a careful study to find out the reasons by examining each of the activities. We note that the cause of the case of cost overruns are the two activities. (A) and (E). Since activity (A) has been completed in full, management cannot take any corrective measures for it, but activity (E) is still in progress, as its completion has reached (25%), so management can take a specific measure to bring the actual costs closer to the budget costs. The administration may seek to reduce the costs of activities (C), (D), (F), and (G) to keep the actual costs of the project within the budget costs.